2001
DOI: 10.1002/pi.640.abs
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution solid‐state NMR investigation of the filler–rubber interaction: 2. High‐speed [1H] magic‐angle spinning NMR spectroscopy in carbon‐black‐filled polybutadiene

Abstract: This work investigates the behaviour of elastomeric chains (polybutadienes of identical molecular weight but different microstructures) in the close vicinity of carbon black surfaces in order to attain a better understanding of the structure and properties of interphases. Elastomer±®ller interactions are assessed through the study of the thermal properties and NMR relaxation characteristics of the corresponding materials. Three series of samples were compared: pure polymers, raw polymer±®ller blends (®ller loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In fact, polymer chain immobility has been thought of as one of the reasons for enhancements in the mechanical properties of polymer nanocomposites. Laboratory experiments as well as molecular dynamics simulations have conjectured that the mobility of polymer chains is hindered when nanoparticles are dispersed in a polymer [17,27,28,29]. As discussed in section 3.1 above, the interactions between polymer chains and nanoparticle lead to the formation of a highly immobile polymer nanolayer close to the nanoparticle surface due to strong bonding of the charged particle surface and the polymer chains [17].…”
Section: Occurrence Of Lower Permittivitymentioning
confidence: 99%
“…In fact, polymer chain immobility has been thought of as one of the reasons for enhancements in the mechanical properties of polymer nanocomposites. Laboratory experiments as well as molecular dynamics simulations have conjectured that the mobility of polymer chains is hindered when nanoparticles are dispersed in a polymer [17,27,28,29]. As discussed in section 3.1 above, the interactions between polymer chains and nanoparticle lead to the formation of a highly immobile polymer nanolayer close to the nanoparticle surface due to strong bonding of the charged particle surface and the polymer chains [17].…”
Section: Occurrence Of Lower Permittivitymentioning
confidence: 99%
“…Research on the mechanical behaviors in polymer nanocomposites has shown significant improvements in several properties [24]. Limited laboratory experiments [37,38] as well as molecular dynamics simulations [39,40] have conjectured that these enhancements in the mechanical characteristics are due to restrictions in the mobility of polymer chains in the nanocomposite caused by the strong interactions of the polymer chains with the highly charged nano-fillers. Depending on the interaction mechanism of the polymer with the nanoparticle, an interfacial polymer nanolayer is reported to form on the nanoparticle surface which is highly immobile due to the strong bonding of the polymer chains and the particle surface [37].…”
Section: Lower Effective Permittivitymentioning
confidence: 99%
“…BdR is considered to be crucial for the processing, rheology, and storage stability of compounds and the mechanical properties of vulcanizates . It may exhibit a T g the same as or very slightly higher than that of the matrix …”
Section: Introductionmentioning
confidence: 99%